Muscimol injection into the ventral posterolateral nucleus of the thalamus impairs tactile reward-seeking behavior but preserves affective vocalization in male rats - Rie Shimoju (PLoS ONE, 2026)
Ultrasonic vocalizations (USVs) are a useful tool for evaluating emotion and motivation in rodents. Rhythmic stroking in rats induces positive affective 50-kHz USVs and reward-seeking behavior. This response involves the dorsal column tract as the ascending pathway; however, supraspinal mechanisms remain unknown. We hypothesized that the ventral posterolateral nucleus of the thalamus (VPL), which receives somatosensory inputs from the spinal cord via the dorsal column–medial lemniscus pathway, might be involved in positive 50-kHz USV production and motivated tactile reward-induced behavior. To test the hypothesis, we used young adult male rats before and after inactivation of the VPL with bilateral infusion of muscimol, a potent γ-aminobutyric acid (GABA)-A type receptor agonist. We measured 50-kHz USVs, approach latency, and spontaneous behaviors pre- and post-muscimol injection, focusing on two emotional (during rhythmic stroking and receiving reward) and motivational (after rhythmic stroking and reward-seeking) conditions. Increased GABAergic inhibition in the VPL completely impaired approach behavior without causing obvious sensory and motor dysfunctions, but only slightly affected 50-kHz USVs. The present data indicate that the GABAergic system in the VPL is substantially involved in execution of reward-seeking behavior but not in the 50-kHz USVs induced by tactile rewards.